2018
DOI: 10.1101/474924
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Host-pathogen coevolution increases genetic variation in susceptibility to infection

Abstract: 35It is common to find considerable genetic variation in susceptibility to infection in natural 36 populations. We have investigated whether natural selection increases this variation by 37 testing whether host populations show more genetic variation in susceptibility to pathogens 38 that they naturally encounter than novel pathogens. In a large cross-infection experiment 39 involving four species of Drosophila and four host-specific viruses, we always found greater 40 genetic variation in susceptibility to vi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Besides, it only reflects the susceptibility of a host to a specific virus under current situation and fail to consider the dynamic interaction process between viruses and hosts. Considering the substantial mutation rates and adaptation abilities of viruses 25 , it is important to evaluate virus infection and transmission capability in a more fundamental manner.…”
Section: Systematically Screening Of Target Cells For 144 Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, it only reflects the susceptibility of a host to a specific virus under current situation and fail to consider the dynamic interaction process between viruses and hosts. Considering the substantial mutation rates and adaptation abilities of viruses 25 , it is important to evaluate virus infection and transmission capability in a more fundamental manner.…”
Section: Systematically Screening Of Target Cells For 144 Virusesmentioning
confidence: 99%
“…Viruses and hosts have been constantly co-evolving for millions of years, which collectively shaped the immune landscape of animals and the host range of viruses 25 .…”
Section: Systematically Screening Of Target Cells For 144 Virusesmentioning
confidence: 99%
“…Host–pathogen interactions are commonly characterized by strong genetic interactions between host and pathogen genotypes ( G × G interactions), particularly with regard to trait variation influenced by steps involving the all‐or‐nothing blocking of infection by the pathogen (Hall et al, ). The co‐evolutionary history of a host and pathogen (novel vs. co‐adapted) also shapes the expression of genetic variation, with the genetic variation in a host's susceptibility to a pathogen likely to be much higher when exposed to pathogens they normally encounter (Duxbury et al, ). Recent work by MacPherson, Otto, and Nuismer () has shown that detection of loci underlying symptoms of disease are, as a result, highly sensitive to the types of host and pathogen genotypes included in a study.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable phenotypic and genetic variation in disease resistance has been documented in natural plant populations (Thrall et al ., ), including forest trees (Bingham et al ., ; Ennos, ). However, different patterns of variation have been predicted or observed in noncoevolved host–pathogen systems (Duxbury et al ., ). In particular, little or no resistance has frequently been reported in naive plant populations (that have had no previous contact with a pathogen) explaining severe epidemics following the introduction of pathogens into areas outside their native zone (Schlarbaum et al ., ; Desprez‐Loustau et al , ).…”
Section: Introductionmentioning
confidence: 97%